Influence of sandblasting and acid etching on fatigue properties of ultra-fine grained Ti grade 4 for dental implants. (November 2020) - Fintová, Stanislava; Kuběna, Ivo; Palán, Jan; Mertová, Kateřina; Duchek, Michal; Hutař, Pavel; Pastorek, Filip; Kunz, Ludvík
Abstract: Commercially pure Ti is a typical material for dental implants. Besides oral environmental effects, implants are seriously mechanically loaded during the lifetime. Mechanical resistance of coarse and ultra-fine grained Ti grade 4 was investigated. Significant grain size refinement resulting in the 65% increase of the proof stress is reported. The fatigue endurance limit increased from 523 MPa to 698 MPa due to grain refinement. The influence of sandblasting combined with acid etching on fatigue damage of both material states was analyzed. The surface treatment was proven as detrimental to the fatigue properties of both material states, due to reduction of the fatigue initiation stage. Nevertheless, the fatigue endurance limit of the surface-treated ultra-fine grained material remained higher than the fatigue endurance limit of the coarse-grained material without surface treatment. Reported results confirm better mechanical resistance of ultra-fine grained materials for dental implants in the comparison with coarse-grain one. Highlights: SLA treatment negatively affects Ti grade 4 fatigue life. Surface fatigue cracks initiation was observed for CG and UFG Ti even after SLA. SLA surface roughness results in the acceleration of fatigue crack initiation. Fatigue endurance limit of SLA UFG Ti remained higher than the one of CG Ti.